53 MAGNETIC RESONANCE SPECTROSCOPY, DIFFUSION TENSOR IMAGING, AND MAGNETIC RESONANCE PERFUSION IN THE EVALUATION OF FIBROMYALGIA PATIENTS: A PROSPECTIVE STUDY. (1st March 2006) - Petrou, M.; Foerster, B.; McLean, S.; Harris, R.; Clauw, D. J.; Sundgren, P. C.
Abstract : Purpose: To determine if there are significant differences between fibromyalgia (FM) patients and healthy controls using three different functional brain imaging techniques to assess for differences in a number of brain areas that have been considered to play a role in pain processing. Materials and Methods: All subjects (20 FM patients and 20 age-matched controls) underwent a conventional pre- and postcontrast MRI as well as completing extensive baseline clinical work-up including the McGill Pain Questionnaire and pain/pressure sensitivity testing. For 2D-CSI proton spectroscopy (TE/TR = 144/1500 ms), 18 1 × 1 × 1 cm voxels were placed in areas implicated in pain processing. Metabolite ratios were calculated for each voxel. DTI was performed using a single-shot spin-echo EPI technique along nine different directions with a b value of 1, 000 s/mm 2 and standardized 50 mm 2 regions of interests (ROIs) were placed in a number of potential pain processing regions. For MR perfusion, 20 50 mm 2 circular ROIs were placed in selected gray and white matter structures to allow calculation of relative quantitative data for mean time to enhance (MTE) and negative enhancement integral (NEI). Student's t -test was used for statistical analysis. Results: Analysis of the 2D-CSI data showed mean Cho/Cr ratios to be significantly higher in FM patients compared to normal controls in the right prefrontal subcortical white matter ( p = .02) and the left parietal white matter ( p = .04). Nonsignificant similar trends were seen in the left thalamus ( p = .07) and the left internal capsule ( p = .09). No significant differences were found in apparent diffusion coefficient (ADC) and fractional anisotropy (FA) values between fibromyalgia patients and normal controls in most of the different regions examined. A tendency for lower FA values was found in the parietal white matter in patients with fibromyalgia compared to the normal healthy controls, 0.256 ± 0.026 (mean ± SD) vs 0.273 ± 0.034, respectively ( p = .06). Regarding MR perfusion, relative MTE values were significantly lower in FM patients compared to healthy controls in the following areas: bilateral insula, thalami, prefrontal dorsolateral gray matter, corona radiata, frontal white matter, parietal white matter, and right internal capsule. Conclusion: Our data suggest that there are differences between FM patients and healthy controls in brain regions that have been implicated in pain processing. Larger studies are needed to better understand the determinants and consequences of CNS changes in FM, correlate with clinical symptoms, and evaluate the potential of functional imaging in disease monitoring and therapy response.